How Journalists Think about Media Effects—And Why We Should Care. Issue 2 (15th March 2017) - Müller, Philipp; Hohlfeld, Ralf
ABSTRACT: Research suggests that journalists' beliefs about media effects are influenced by unsystematically gathered knowledge and subjective-intuitive judgments. However, it has also been shown that these presumptions must be considered important factors for the formation of journalistic coverage. Against this background, this article synthesizes existing research on dimensions, determinants, and consequences of journalists' presumptions of media effects. The resulting framework offers researchers in the field of journalistic content production a comprehensive overview of the possible role that presumptions of media effects could play for journalistic content creation. In a second step, we summarize the implications that the current state of research points at. We discuss why journalism scholars should integrate presumed media effects into their research agendas and what communication researchers, as well as journalists themselves, could do to promote more realistic beliefs about media effects among journalists.